Unwind : UnSouled - Book 3 - Shusterman, Neal (New York : Simon & Schuster BFYR, 2013)
After the destruction of the Graveyard, Connor and Lev are on the run, seeking a woman who may be the key to bringing down unwinding forever while Cam, the rewound boy, tries to prove his love for Risa by bringing Proactive Citizenry to its knees.
830L
Accelerated Reader AR
Keywords: Fugitives from justice; Juvenile fiction; Survival; Juvenile fiction; Revolutionaries; Juvenile fiction; Identity (Psychology) -- Juvenile fiction; Fugitives from justice; Fiction; Survival; Fiction; Revolutionaries; Fiction; Identity; Fiction; Science fiction